Love, literature, and the quantum atom: Niels Bohr's 1913 trilogy revisited - Aaserud, Finn (Oxford University Press, 2013)
This title presents unpublished excerpts from extensive correspondence between Niels Bohr and his immediate family, and uses it to describe and analyze the psychological and cultural background to his invention of the quantum theory of the atom --